Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/d0sc05002d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled hierarchical self-assembly of networked coordination nanocapsulesviathe use of molecular chaperones

Abstract: Molecular chaperones play a critical role in directing the assembly of nanocapsules that assemble into 2D or 3D coordination networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Inspired by living organisms, where hierarchical proteins with metal ions like Fe, Mn, or Cu can be efficiently formed with the aid of supramolecular chaperones, 63,64 herein we introduce proline as the molecular chaperone, which can capture, protect, and insert Mn II ions into the framework. 51 The synthesis of CP-MONCs has been accomplished by employing PgC 3 OH, Mn II ions, and proline using a solvothermal method. Moreover, upon increase of the water content in the reaction mixture, the resulting assemblies transform from 2D (11) to 3D (12) CP-MONCs (Figure 7).…”
Section: Coordination Polymers Based On Hexameric Moncsmentioning
confidence: 99%
“…Inspired by living organisms, where hierarchical proteins with metal ions like Fe, Mn, or Cu can be efficiently formed with the aid of supramolecular chaperones, 63,64 herein we introduce proline as the molecular chaperone, which can capture, protect, and insert Mn II ions into the framework. 51 The synthesis of CP-MONCs has been accomplished by employing PgC 3 OH, Mn II ions, and proline using a solvothermal method. Moreover, upon increase of the water content in the reaction mixture, the resulting assemblies transform from 2D (11) to 3D (12) CP-MONCs (Figure 7).…”
Section: Coordination Polymers Based On Hexameric Moncsmentioning
confidence: 99%
“…Other bowl-shaped host molecules of the calixarene-family have also been shown to form MOFs/coordination polymers with embedded metallo-capsules, 6 and Atwood and co-workers have also reported much larger network nano-cages with pyrogallol [4]arene hosts. 7 Holman et al have also reported a coordination chain material with embedded cryptophanes which are organic CTV-based capsules. 36 The earliest examples with CTV-ligands were the series [Ag 3 (L10) 2 (CH 3 -CN) 3 Cl]•2X•n(CH 3 CN) where X = BF 4 , AsF 6 or ClO 4 .…”
Section: Linked Capsules and Cagesmentioning
confidence: 99%
“…This is also the case for networked coordination capsules and coordination cages with other host molecules. 6,7 As for the CTV examples, these included networks of vertex-linked capsules as well as those linked by an additional ligand. Examples of post-synthetic assembly of showing the 2D network of Ag 3 L 2 capsules linked by μ 3 -Cl − (larger olive spheres) and inset is side-view of one capsule highlighting that the μ 3 -Cl − are endo to the cage.…”
Section: Linked Capsules and Cagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19‐26 ] Low‐symmetry architectures such as crowns and bowls are difficult to design and synthesis. [ 27‐29 ] Only a few coordination complexes could be described as molecular bowls. [ 29‐31 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%